On the identity of Tettigonia krugeri Massa from Libya with some remarks on variability of Tettigonia species (Orthoptera: Tettigoniidae; Tettigoniinae) - Massa, Bruno; Tagliavia, Marcello (Zootaxa, 2019)
Morphological and genetic data allowed the authors to resurrect the name Tettigonia krugeri Massa, 1998 as a valid species. It is currently known only from two specimens (one male and one female) collected in Cirenaica (Libya).